Analysis of the Use of the Halo Bahasa Application PASTI Feature on Knowledge of Indonesian Language Equivalents - Alfiana, Tanti; Safar, Muh.; Srimularahmah , Andi (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study was motivated by the importance of understanding Indonesian language equivalents for students in improving language literacy. Until now, students still face obstacles in finding the right equivalents due to the limited availability of easily accessible learning resources. To address this issue, this study utilizes the Halo Bahasa PASTI feature as a technology-based learning medium. This study uses a qualitative method with a case study approach. The research subjects are students of SMA Negeri 14 Bone, selected based on ease of access and suitability with the research objectives. Data were collected through knowledge tests, observations, and documentation, then analyzed to describe the application implementation process, students' ability to use it, and students' knowledge of equivalent terms after using the application. The results of the study show that the implementation of the Halo Bahasa PASTI application went quite well. Most students were able to download, install, and operate the application independently, although some still needed further guidance. Students' ability to use the application was relatively good, especially in typing foreign terms, determining the search domain, and finding appropriate equivalents. From the knowledge test results, the majority of students achieved moderate to high scores, so it can be concluded that the use of the application contributed to improving students' understanding of Indonesian term equivalents.